Outcomes of Reconstruction of the Stage II Adult Acquired Flatfoot Deformity in Older Patients. Issue 2 (10th April 2018) - Conti, Matthew; Jones, Mackenzie; Nguyen, Joseph; Deland, Jonathan; Ellis, Scott
Category: Hindfoot Introduction/Purpose: Reconstruction of the stage II adult acquired flatfoot deformity (AAFD) often requires the use of multiple osteotomies and soft-tissue procedures that may not heal well in older patients potentially leading to persistent pain, recurrent flatfoot symptoms, and the need to revise or fuse these patients at a higher rate than younger patients. Thus, some surgeons may advocate performing a double/triple arthrodesis in older patients with severe flexible deformity (Pinney and Lin, FAI 2006). No studies have investigated the clinical outcomes of flatfoot reconstructions in this population. The purpose of our study was to determine whether patients older than 65 years old with stage II AAFD had inferior clinical outcomes or an increased number of subsequent surgical procedures following flatfoot reconstruction when compared with younger patients. Methods: One-hundred and forty consecutive feet (70 right, 70 left) in 137 patients from the authors' institution who underwent a reconstruction for stage II AAFD performed between January 2007 and March 2015 were eligible for this retrospective study (mean 57.3 years old, range 22.9 to 81.6 years old). Patients were divided into three groups based on age: less than 45 years old (young) (n=20), 45 to 65 years old (middle-aged) (n=88), and 65 years old and older (older) (n=32). Preoperative and postoperative clinical outcomes at a minimum of 2.0 years (mean 3.2 years) were compared using the using the Foot and Ankle Outcome Score (FAOS), which has been validated for AAFD. Hospital records were reviewed to determine if patients underwent a subsequent procedure. One-way ANOVA tests were used to compare the mean change in FAOS scores, and Chi-squared tests were used to compare the number of subsequent procedures for each group. Results: Older patients did not demonstrate any differences in changes in FAOS subscales compared with younger patients (all p- values>0.18) (Figure 1). The mean improvement in the FAOS pain, symptoms, daily activities, sports activities, and quality of life for the older group was 22.8 (p-value=0.50), 12.8 (p-value=0.48), 15.1 (p-value=0.19), 23.3 (p-value=0.45), and 38.1 (p-value=1.0), respectively, which was not different than the mean improvement in younger patients. Additionally, patients in the older group were not more likely to undergo a subsequent arthrodesis (p-value=0.18), revision surgery (p-value=0.65), or removal of hardware (p-value=0.15) than the younger patients. Two patients (6.3%) in the older cohort required a revision of their flatfoot reconstruction compared with nine patients (10.2%) in the middle-aged group and one patient (5.0%) in the young group. Conclusion: Our study indicates that patients over the age of 65 years old with stage II AAFD have improvements in patient- reported outcomes following surgical reconstruction that are not significantly different than younger patients. Additionally, older patients are not more likely to undergo a subsequent arthrodesis, revision procedure, or removal of hardware than patients in the younger cohorts. These results suggest that joint-preserving reconstruction of the stage II AAFD may be performed in older patients with acceptable outcomes.